2014
DOI: 10.1371/journal.ppat.1004423
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Structural Constraints on EBNA1 Synthesis Impact on In Vivo Antigen Presentation and Early Priming of CD8+ T Cells

Abstract: Recent studies have shown that virally encoded mRNA sequences of genome maintenance proteins from herpesviruses contain clusters of unusual structural elements, G-quadruplexes, which modulate viral protein synthesis. Destabilization of these G-quadruplexes can override the inhibitory effect on self-synthesis of these proteins. Here we show that the purine-rich repetitive mRNA sequence of Epstein-Barr virus encoded nuclear antigen 1 (EBNA1) comprising G-quadruplex structures, limits both the presentation of MHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…Furthermore, destabilisation of these G4 structures, following transfection of a vector expressing native GAr mRNA fused to a sequence encoding an ovalbumin epitope, resulted in enhanced antigen presentation of that epitope by a T-cell hybridoma [ 57 ]. These results have been mimicked with the EBNA1 antigen itself in an in vivo mouse model, where EBNA1 mRNA G4 destabilisation resulted in enhanced antigen presentation by dendritic cells and the early priming of CD8+ T cells [ 58 ], demonstrating that reducing the translation efficiency of viral proteins is a key part of the latency program of this gammaherpesviruses.…”
Section: Could G4s Play a Role In Viral Latency?mentioning
confidence: 99%
“…Furthermore, destabilisation of these G4 structures, following transfection of a vector expressing native GAr mRNA fused to a sequence encoding an ovalbumin epitope, resulted in enhanced antigen presentation of that epitope by a T-cell hybridoma [ 57 ]. These results have been mimicked with the EBNA1 antigen itself in an in vivo mouse model, where EBNA1 mRNA G4 destabilisation resulted in enhanced antigen presentation by dendritic cells and the early priming of CD8+ T cells [ 58 ], demonstrating that reducing the translation efficiency of viral proteins is a key part of the latency program of this gammaherpesviruses.…”
Section: Could G4s Play a Role In Viral Latency?mentioning
confidence: 99%
“…The presence of G4s in viruses and their involvement in virus key steps is increasingly evident in most of the Baltimore groups [10,11]. In the dsDNA group, G4s were described in both Herpesviridae and Papillomaviridae families [12][13][14][15][16][17][18][19][20]. In ssDNA viruses, the presence of G4s was reported in the adeno-associated virus genome [21].…”
mentioning
confidence: 99%
“…Such observations resulted from a number of studies on EBNA1 over the last decade that showed that in spite of the inhibitory effect of the internal GAr domain, CTL responses directed towards EBNA1 could be readily detected in EBV seropositive individuals [ 7 , 46 , 47 ], and we could observe SIINFEKL-specific CTLs after DNA immunization with aLANA-SIIN ( Fig 10 ). This paradox was resolved following extensive in vitro molecular analyses of the endogenous processing of EBNA1 indicating that CTL epitopes from this protein were predominantly generated from newly synthesized DRiPs rather than from the long-lived pool of stable EBNA1 in EBV-infected B cells [ 23 , 26 28 , 41 , 47 ]. These observations have subsequently been further extended to demonstrate that the generation of DRiPs is intrinsically linked to the rate at which proteins are synthesized [ 23 ].…”
Section: Discussionmentioning
confidence: 99%